1991
DOI: 10.1021/j100166a060
|View full text |Cite
|
Sign up to set email alerts
|

Anodic underpotential deposition and cathodic stripping of iodine at polycrystalline and single-crystal gold: studies by LEED, AES, XPS, and electrochemistry

Abstract: The oxidative chemisorption and cathodic stripping reductive desorption of iodine have been compared at smooth polycrystalline and well-defined Au( 1 1 1) singlacrystal electrodes. Experimental measurements were based upon cyclic voltammetry, thin-layer coulometry, X-ray photoelectron spectroscopy, Auger electron spectroscopy, and low-energy electron diffraction. The results indicate that iodide is oxidatively adsorbed as zerovalent atomic iodine at potentials between -0.4 V and +0.4 V (Ag/AgCl reference); at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
64
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(80 citation statements)
references
References 3 publications
15
64
1
Order By: Relevance
“…Under a high positive electric field, these fragments can lose one or more hydrogen atoms and form lighter ions. Notably, clear evidence in the low-mass region can be found for molecular fragments associated with C 1 H x (14-15), C 2 H x (27-29), C 3 H x (36)(37)(38), and C 4 H x (55-56). There is also evidence for sulfur-containing species, such as S (32) and SCH x (44-46).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Under a high positive electric field, these fragments can lose one or more hydrogen atoms and form lighter ions. Notably, clear evidence in the low-mass region can be found for molecular fragments associated with C 1 H x (14-15), C 2 H x (27-29), C 3 H x (36)(37)(38), and C 4 H x (55-56). There is also evidence for sulfur-containing species, such as S (32) and SCH x (44-46).…”
Section: Resultsmentioning
confidence: 99%
“…With an approximated detector efficiency of 50%, this number is comparable to the ion density values determined for iodide-covered gold surfaces from STM or LEED. 35,38 Notably, iodide surface densities of 4.6 and 4 ions nm -2 for the Au (111) and Au (100) surfaces are expected based upon a surface coverage of ∼0.3 monolayers, which is typical for adsorption from aqueous solutions. These results demonstrate the ability to detect a single monolayer of adsorbed ions on the surface of this gold specimen using the 3DAPT.…”
Section: Resultsmentioning
confidence: 99%
“…The broad response in the wide potential range of ca. −0.5 to −0.9 V is due to the reversible adsorption/deposition of I − [38]. The current in the potential zone of 0-0.2 V is diminished owing to the inhibition of chemisorption of OH − by I-adlayer [37].…”
Section: Optimization Of the Conditionsmentioning
confidence: 99%
“…In the presence of 0.1 mM KI ( Fig. 1(b)), the amplitude and broadness of the redox peak at −0.32 V corresponding to the UPD of Pb at the Au(1 1 1) domain increase due to the overlapping with the adsorption/deposition of I − [38], while the redox peak at −0.17 V is inhibited by the adsorbed I − [39]. The broad response in the wide potential range of ca.…”
Section: Optimization Of the Conditionsmentioning
confidence: 99%
“…3d. The I3d 5/2 for I 2 @PANI-CdS appears as one strong peak at 618.6, which can be attributed to triiodide (I 3 -) [36][37][38]. To study the photoresponse of the as-prepared electrode, the photocurrent generation is observed in the presence of CdS, PANI-CdS and I 2 @PANI-CdS ITO electrodes with Na 2 SO 3 solution (1 M, pH 12) as a sacrificial donor under visible-light ( = 420 nm) irradiation.…”
Section: Characterizationmentioning
confidence: 99%